Daily Spatial Mobilities : Physical and Virtual. - Kellerman, Aharon (Transport and mobility series., 2012)
Outlining his argument for daily spatial mobility, author Aharon Kellerman focuses on needs and triggers for daily mobilities, on levels of personal mobility and personal autonomy in daily mobilities and on potential mobilities leading to practiced ones. The concept is further explored using three major types of daily mobility, terrestrial, virtual and aerial and three major spatial elements; urban spatial reorganization in the information age, mobility terminals, namely bus, metro, and railway stations as well as airports, and global opportunities through daily mobilities, notably for users o.